117 Optimisation and Reproducibility of 18F-Fluoride Positron Emission Tomography and Computed Tomography in Patients with Aortic Stenosis. (3rd June 2016) - Pawade, Tania; Cartlidge, Timothy; Newby, David; Marc, Dweck
Abstract : Background: 18F-Fluoride positron emission tomography (PET) and computed tomography (CT) can measure disease activity and progression in aortic stenosis. We aimed to optimise imaging methodology, analysis and scan-rescan reproducibility. Methods: Fifteen patients with aortic stenosis underwent 18F-fluoride PET-CT twice within 1 month. We compared non-gated PET and non-contrast CT, with a modified approach that incorporated contrast CT and ECG-gated PET. We explored a range of image analysis techniques including estimation of blood pool activity at differing vascular sites and a most-diseased segment (MDS) approach. Results: Contrast-enhanced ECG-gated PET-CT provided superior spatial localisation of 18F-fluoride uptake that permitted localisation to individual valve leaflets (Figure ). Scan-rescan reproducibility was markedly improved using enhanced analysis techniques leading to a reduction in variability from 25% to <10% (tissue-to-background MDS: mean value 1.55, difference 0.05, limits of agreement -0·10 to 0·20). Conclusion: Optimised 18F-fluoride PET-CT provides excellent spatial resolution and scan-rescan reproducibility. It holds major promise as a marker of disease activity in aortic stenosis and has major potential as a biomarker end-point of trials of novel therapies in aortic stenosis.